Dermatitis Linearis: Vesicating Dermatosis Caused by Paederus Species (Coleoptera: Staphylinidae). Case Series and Review (2013)
Objective: Outbreaks of dermatitis linearis have been documented worldwide. We present a case series of dermatitis linearis from Latin America to highlight the importance of this clinical entity. Clinical, historical, epidemiological, and pathological aspects of the condition are discussed, and a concise current approach to the management and treatment of this morbidity is presented. Methods: We present a series of 4 selected cases reflecting the clinical spectrum exhibited in dermatitis linearis by Paederus along with a review of the literature. Results: In this review we demonstrate the need for awareness of dermatitis linearis as a clinical entity that must be considered in the broad list of differential diagnosis embracing vesicating linear lesions. Conclusions: Capture of the insect, epidemiologic features, and a high clinical suspicion can aid in making the correct diagnosis. Primary prevention through public awareness, decreased use of artificial lighting, and mosquito nets can limit the extent and severity of outbreaks. © 2013 Wilderness Medical Society.